Canine heartworm disease (dirofilariosis): pathogenesis and diagnosis of a multidimensional disease - SINANIS (Θ.Ν. ΣΙNΑΝΗΣ) T. N.; KOUTINAS (Χ.Κ. ΚΟΥΤΙΝΑΣ) C. K.; DIAKOU (Α. ΔΙΑΚΟΥ) A.; PAPADOPOULOU (Π. ΠΑΠΑΔΟΠΟΥΛΟΥ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
Canine heartworm disease (dirofilariosis) caused by Dirofilaria immitis is a parasitic disease frequently occurring in the para-Mediterranean countries. Global climate changes, animal transportation and inappropriate implementation of preventive measures in companion animals are some factors that have contributed to expansion of the disease in the last decades. Transmission of the parasite is carried out by mosquitoes, whilst the final hosts are members of the Canidae family or occasionally other animal species and humans. Apart from the endothelial lesions caused by the adult filariae, the endosymbiotic bacterium Wolbachia pipientis appears to play a role in the pathogenesis of the disease, through endotoxin production and production of specific IgG responses by the host against the bacterium’s surface proteins. Based on clinical and laboratory findings, dogs with the disease can be categorized into one of four clinical stages, ranging from asymptomatic to caval syndrome. Diagnosis of the disease can be reached after evaluation of clinical findings, in conjunction with paraclinical examinations, e.g., microfilarial and antigen testing, diagnostic imaging, haematological and blood biochemical examination.